1996
DOI: 10.1017/s0252921100049447
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Gas in Bright Barred Spiral Galaxies: Hα Images

Abstract: In this paper we present the spatial distribution of ionized hydrogen gas, Hα, in a set of 52 bright barred Shapley-Ames spiral galaxies. In summary we were able to detect Hα line emission from distinct regions in the galaxies as from compact nuclei, from circumnuclear rings, from the bar, from ends of bars, from inner rings, from spiral arms, from outer rings and from places or structures perpendicular either to the bar or to the spiral arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 8 publications
3
71
0
Order By: Relevance
“…In our sample, we see that the strongest bars (Q b,NGC1073 =0.63 and Q b,NGC5112 =0.62) show Hα emission, but further study is needed to see if this emission is located in the regions of high shocks/shear. (ii) García-Barreto et al (1996) found that the barred galaxies with Hubble types SBa or earlier in their sample did not show Hα emission, probably due to the low gas content available for inflow (which is not the case, for example, for NGC 4151) so the morphological type is not in principle the only reason. (iii) Martin & Friedli (1997) also found that the two highest SFRs correspond to the galaxies which present the strongest signs of recent interaction or merging (NGC 4731 and NGC 7479).…”
Section: Bar-induced Non-circular Motionsmentioning
confidence: 94%
“…In our sample, we see that the strongest bars (Q b,NGC1073 =0.63 and Q b,NGC5112 =0.62) show Hα emission, but further study is needed to see if this emission is located in the regions of high shocks/shear. (ii) García-Barreto et al (1996) found that the barred galaxies with Hubble types SBa or earlier in their sample did not show Hα emission, probably due to the low gas content available for inflow (which is not the case, for example, for NGC 4151) so the morphological type is not in principle the only reason. (iii) Martin & Friedli (1997) also found that the two highest SFRs correspond to the galaxies which present the strongest signs of recent interaction or merging (NGC 4731 and NGC 7479).…”
Section: Bar-induced Non-circular Motionsmentioning
confidence: 94%
“…6) García-Barreto et al 1996a, 1996b. CO contours are at À3, 3, 5, 7, 9, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 35, 40, 45, 50, 60, and 70 ; 150 mJy km s À1 .…”
Section: Gas Kinematics and Dynamical Massmentioning
confidence: 99%
“…Figures 3 and 4 show the total CO line flux integrated over 300 km s À1 , superposed on the H +[N ii] (continuumsubtracted) and I-band images (García- Barreto et al 1996aBarreto et al , 1996b. The strongest CO emission (65 ) arises at the compact nucleus and from a circumnuclear structure (see below).…”
Section: The Nuclear Regg Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryder & Dopita (1994) studied the relative scale lengths of Hα, V-and I-band emission from 34 S0-Sm galaxies, finding the line emission to have larger scale lengths than those of the continuum emission. García-Barreto et al (1996) investigated Hα imaging of 52 barred spiral galaxies, finding nuclear rings in 10, and emission indicating SF along the bar in 18. Dale et al (2001) analysed Hα extents of galaxies normalised by their I-band sizes, finding no strong type dependences; similar results for Hα to R-band scalelength ratios were found by Koopmann & Kenney (2004) and Koopmann et al (2006).…”
Section: Introductionmentioning
confidence: 99%